Biosourced cyclosophoraose-driven acceleration of click reaction in H2O - Cho, Eunae; Jeong, Daham; Dindulkar, Someshwar D.; Jung, Seunho (Journal of industrial and engineering chemistry (Seoul, Korea), 2018)
[Display omitted] •A facile synthetic strategy of 1,4-disubstituted-1,2,3-triazoles in H2O is reported.•Cyclosophoraoses purified from Rhizobium species promoted the click reaction of azide and alkyne in water.•The supramolecular catalytic system provides a simple, workup-free, and green catalytic platform for aqueous click reaction. Here, we report biosourced cyclosophoraose (CyS)-promoted click reaction of organic azides and alkynes in water, where CyS, rhizobial cyclic β-1,2 glucan molecules containing 17–23 glucoses, dramatically decreased the reaction time from hours to minutes via the solubilization of aromatic alkynes. This catalytic system was successfully applied to the copper-mediated Huisgen 1,3-dipolar cycloaddition reaction using in situ-generated azide. The developed strategy yielded 1,4-disubstituted-1,2,3-triazoles after a short reaction time without bases from a room-temperature aqueous medium, and the products were purified simply by precipitation without requiring further column purifications.